2013
DOI: 10.1039/c3lc50802a
|View full text |Cite
|
Sign up to set email alerts
|

Probing cell traction forces in confined microenvironments

Abstract: Cells migrate in vivo within three-dimensional (3D) extracellular matrices. Cells also migrate through 3D longitudinal channels formed between the connective tissue and the basement membrane of muscle, nerve, and epithelium. Although traction forces have been measured during 2D cell migration, no assay has been developed to probe forces during migration through confined microenvironments. We thus fabricated a novel microfluidic device consisting of deflectable PDMS microposts incorporated within microchannels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…The ability of glioma cells to migrate through spatial restrictions has also been attributed to the volume-regulating ability of the sodium-potassium-chloride cotransporter isoform 1 (52). However, it remains to be elucidated whether traction forces generated by glioma cells are relevant in channels of even smaller cross-sectional area, since we have observed a reduced role for traction forces during osteosarcoma cell migration in channels that are 10 m wide ϫ 4 m high (114). Meanwhile, in wide channels (20 m wide ϫ 25 m high or 40 m wide ϫ 25 m high) or on 2D substrates, glioma cell migration speed is biphasic with matrix stiffness, with optimum migration at an ECM stiffness of ϳ10 kPa (106), a trend that has previously been reported for numerous cell types, including neutrophils (129), smooth muscle cells (110), and epithelial cells (30).…”
Section: C102 Physical Cues In Tumor Cell Migrationmentioning
confidence: 88%
See 2 more Smart Citations
“…The ability of glioma cells to migrate through spatial restrictions has also been attributed to the volume-regulating ability of the sodium-potassium-chloride cotransporter isoform 1 (52). However, it remains to be elucidated whether traction forces generated by glioma cells are relevant in channels of even smaller cross-sectional area, since we have observed a reduced role for traction forces during osteosarcoma cell migration in channels that are 10 m wide ϫ 4 m high (114). Meanwhile, in wide channels (20 m wide ϫ 25 m high or 40 m wide ϫ 25 m high) or on 2D substrates, glioma cell migration speed is biphasic with matrix stiffness, with optimum migration at an ECM stiffness of ϳ10 kPa (106), a trend that has previously been reported for numerous cell types, including neutrophils (129), smooth muscle cells (110), and epithelial cells (30).…”
Section: C102 Physical Cues In Tumor Cell Migrationmentioning
confidence: 88%
“…Using this device, we found that, consistent with a decreased dependence on adhesion, tumor cell migration in narrow channels leads to decreased cell traction forces. On 2D surfaces, focal adhesion formation and traction force generation are integral steps in the cell migration process (98); however, human osteosarcoma cells migrating in narrow channels exert significantly reduced traction forces compared with migration in wide, unconfining channels (114). As expected, in wide channels (50 m wide ϫ 4 m high), inhibition of myosin II (via blebbistatin) diminishes cell traction forces, while inhibition of protein phosphatases (via calyculin A, which enhances myosin light chain phosphorylation) increases cell traction forces.…”
Section: C102 Physical Cues In Tumor Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, engineered surfaces, created using micropatterning, permit manipulation and control of the substrate stiffness, topographic features, and anisotropy. [3][4][5][6][7] To explore the effects of geometric patterning on cells, Parker and colleagues used micro-contact printing to create adhesive islands of different sizes and shapes and measured tractions for individually constrained cells. 8 They showed that traction forces were highest in sharp corners where cellular processes were also directed.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies demonstrated that broblasts conned within narrow channels developed lower tractions and had lower migration speeds as compared to cells in wide channels. 4 Cellular connement within channels is however not representative of the in vivo three dimensional tissue milieu of cells which consists of adherent polarized cells located in an organized and anisotropic extracellular matrix. To explore the role of substrate anisotropy in cell tractions and migrations, Tymchenko and co-workers designed a silicon substrate with surface topographical cues, created using photolithography and deep reactive ion etching, to obtain an array of vertical pillars between solid ridges.…”
mentioning
confidence: 99%